Recent studies of the distribution and abundance of grey seals (Halichoerus grypus) in north Norway, and their possible influence on parasitic infestations in fish - Haug, Tore; Henriksen, Gunnar; Nilssen, Kjell Tormod; Ørjebu, Alfred (ICES, 1991)
Distributions of grey seals Halichoerus grypus were studied during aerial and ground surveys in North Norway. Surveys were conducted from Lofoten to the Soviet border during the moult (March-April, Finnmark) and breeding (October-December, whole area) periods in 1988-1991. Numbers of grey seals seem to have increased during the past 25-30 years, and the present minimum total estimates are approximately 200 animals in Lofoten, none in Vesterålen, 110 in Troms and 550 in Finnmark. Breeding occurs at a number of sites along the coast, with a delay in the start of the breeding period along a south-north axis. In Lofoten breeding occurs mainly in the first half of October, in Troms/western Finnmark in the middle of November, and in eastern Finnmark in December. Considerable variations were observed in the degree of cod worm Pseudoterranova decipiens infestations in cod Gadus morhua captured near grey seal breeding sites. There was large variability both from year to year and between areas within the same year. Variations in food habits (e.g., change from demersal to pelagic food chains) of the grey seals (known to be important vectors for cod worm) may have contributed to the observed differences.